Ethnosocial profile of Tuvans - Valeriya S. Kan (Novye Issledovaniâ Tuvy, 2016)
The article examines the ethnosocial profile of contemporary Tuvans, with a focus on the dynamics of population change, human environment, self-consciousness, interethnic relations and language command. Our study was based on the official data of the Federal Census and the current statistics we obtained from Tuva territorial branch of the Federal State Statistics Service, as well as on the outcomes of the opinion polls held by a team lead by the author in 2008-2015.